The Witch’s Flight: The Cinematic, the Black Femme, and the Image of Common Sense - Keeling, Kara (Duke University Press, 2007)
Kara Keeling contends that cinema and cinematic processes had a profound significance for twentieth-century anticapitalist Black Liberation movements based in the United States. Drawing on Gilles Deleuze’s notion of “the cinematic”—not just as a phenomenon confined to moving-image media such as film and television but as a set of processes involved in the production and reproduction of social reality itself —Keeling describes how the cinematic structures racism, homophobia, and misogyny, and, in the process, denies viewers access to certain images and ways of knowing. She theorizes the black femme as a figure who, even when not explicitly represented within hegemonic cinematic formulations of raced and gendered subjectivities, nonetheless haunts those representations, threatening to disrupt them by making alternative social arrangements visible.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Queer Times, Black Futures - Kara Keeling (Sexual Cultures, 2019)
Finalist, 2019 Lambda Literary Award in LGBTQ StudiesA profound intellectual engagement with Afrofuturism and the philosophical questions of space and time Queer Times, Black Futures considers the promises and pitfalls of imagination, technology, futurity, and liberation as they have persisted in and through racial capitalism. Kara Keeling explores how the speculative fictions of cinema, music, and literature that center black existence provide scenarios wherein we might imagine alternative worlds, queer and otherwise. In doing so, Keeling offers a sustained meditation on contemporary investments in futurity, speculation, and technology, paying particular attention to their significance to queer and black freedom.Keeling reads selected works, such as Sun Ra's 1972 film Space is the Place and the 2005 film The Aggressives, to juxtapose the Afrofuturist tradition of speculative imagination with the similar “speculations” of corporate and financial institutions. In connecting a queer, cinematic reordering of time with the new possibilities technology offers, Keeling thinks with and through a vibrant conception of the imagination as a gateway to queer times and black futures, and the previously unimagined spaces that they can conjure.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 5-Identités diasporiques; _Nettoyé

Construction of Computation and Desire: Introduction to Yvonne Welbon’s Interview with Pamela L. Jennings - Keeling, Kara (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Early in the following interview, Pamela Jennings explains to Yvonne Welbon that her work gradually expanded from an initial and abiding interest in street photography toward working with and through forms of computational media. Jennings equates her move toward what she describes as “computational-based creative expression” with her growing interest in multimedia throughout the early 1990s, and she uses the term multimedia as a way of marking her work in a variety of different media and her interest specifically in computational media because the formulation computational media was not available to her then. The compelling relationship Jennings narrates between her
Keywords: 1-Cinéma; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé